Processing Yield Percentage and Phytochemical Appraisement of the Leaf, Stem-Bark, Inflore-infructescence, and Root of Petiveria alliacea (Linneaus) - J.O., Arogbodo; F.O., Igbe; I.B., Osho; I.A., Adebayo (International Journal of Scientific Research in Biological Sciences, 2021)
The numerous pharmacological benefits of Petiveria alliacea Linneaus (Guinea Hen Weed) accentuated its further experimental studies, wherewith investigation of the sample processing yield percentage (SPY) and the phytochemical analyses of its leaf (LF), inflore-infructescence (INFLT), stem-bark (SB), and root were carried out using standard methods. Data were analyzed using IBM SPSS version 23 and results were presented as standard deviation (± SD) of duplicate determinations. The samples’ processing yield (SPY) percentage result flows in the order stem-bark > root > inflore-infructescence > leaf indicating the highest (50.60 %) and the least (21.32 %) values obtained in the stem-bark and leaf preparations respectively. The phytochemical screening showed the evaluated plant parts to possess abundant phytochemicals (tannins, saponins, flavonoids, terpenoids, steroids, glycosides, and alkaloids) at varying amount with the INFLT and the R taking the lead. Keen observation divulged the seven phytochemicals screened to be present in the INFLT while other parts did not have them in full. This may be suggesting the INFLT as a better granary of phytochemicals than the other parts. It was concluded that all the parts of P. alliacea are bountiful sources of plants’ secondary metabolites thereby justifying the fantastic use of the plant in folkloric medicine with special reference to the INFLT ampleness in glycosides and alkaloids. Additionally, the INFLT was recommended to be given unflinching attention in further experiments. The leaf also is to be more preferred (owing to its ability to re-sprout after several plucking) when the need for large quantity of extract is inevitably mandatory.